Dynamic sequence evolution of a sex-Associated b chromosome in lake Malawi cichlid fish - Clark, Frances E.; Conte, Matthew A.; Ferreira-Bravo, Irani A.; Poletto, Andreia B. [UNESP]; Martins, Cesar [UNESP]; Kocher, Thomas D. (Oxford University Press (OUP), 2017)
B chromosomes are extra chromosomes found in many species of plants, animals, and fungi. B chromosomes often manipulate common cellular processes to increase their frequency, sometimes to the detriment of organismal fitness. Here, we characterize B chromosomes in several species of Lake Malawi cichlid fish. Whole genome sequencing of Metriaclima zebra Boadzulu individuals revealed blocks of sequence with unusually high sequence coverage, indicative of increased copy number of those sequences. These regions of high sequence coverage were found only in females. SNPs unique to the high copy number sequences permitted the design of specific amplification primers. These primers amplified fragments only in Metriaclima lombardoi individuals that carried a cytologically identified B chromosome (B-carriers), indicating these extra copies are located on the B chromosome. These same primers were used to identify B-carrying individuals in additional species from Lake Malawi. Across 7 species, a total of 43 B-carriers were identified among 323 females. B-carriers were exclusively female; no B chromosomes were observed in the 317 males surveyed from these species. Quantitative analysis of the copy number variation of B-specific sequence blocks suggests that B-carriers possess a single B chromosome, consistent with previous karyotyping of M. lombardoi. A single B chromosome in B-carriers is consistent with 2 potential drive mechanisms: one involving nondisjunction and preferential segregation in a mitotic division prior to the germ-line, and the other involving preferential segregation during meiosis I.
Keywords: Nondisjunction; Preferential segregation; Selfish genetic element; Supernumerary chromosome